Catalytic Chemical Vapor Deposition of Methane to Carbon Nanotubes: Copper Promoted Effect of Ni/MgO Catalysts - Wen Yang; Yanyan Feng; Wei Chu (Journal of Nanotechnology)
The Ni/MgO and Ni-Cu/MgO catalysts were prepared by sol-gel method and used as the catalysts for synthesis of carbon nanotubes by thermal chemical vapor deposition. The effect of Cu on the carbon yield and structure was investigated, and the effects of calcination temperature and reaction temperature were also investigated. The catalysts and synthesized carbon materials were characterized by temperature programmed reduction (TPR), thermogravimetric analysis (TGA), and scanning electron microscopy (SEM). Results showed that the addition of Cu promoted the reduction of nickel species, subsequently improving the growth and yield of CNTs. Meanwhile, CNTs were synthesized by the Ni/MgO and Ni-Cu/MgO catalysts with various calcination temperatures and reaction temperatures, and results suggested that the obtained CNTs on Ni-Cu/MgO catalyst with the calcination temperature of 500°C and the reaction temperature of 650°C were of the greatest yield and quantity of 927%.